The scales of general well-being (SGWB) - Longo, Ylenio; Coyne, Iain; Joseph, Stephen (Elsevier, 2017)
This paper presents the development and validation of a new well-being questionnaire: the Scales of General Well-Being (SGWB). A review of current measures identified fourteen common constructs as lower-order indicators of well-being: happiness, vitality, calmness, optimism, involvement, self-awareness, self-acceptance, self-worth, competence, development, purpose, significance, self-congruence and connection. Three studies were then conducted. In study 1, the item pool was developed and the adequacy of its content to assess each of the fourteen constructs was evaluated by consulting a panel of six subject expert academics. In study 2, the dimensionality was assessed in an adult North American sample (N = 560). The results supported the hierarchical factor structure. In study 3, further evidence confirmed the factor structure, and provided support for the measure’s internal and test-retest reliability, measurement invariance across gender, age and a longitudinal period of 5 weeks, and criterion validity in an adult North American sample (N = 1,101). The SGWB promises to be a useful research tool that provides both a global measure of well-being as well as a collection of fourteen individual health-related scales.